PENGARUH METODE MEMBACA TERBIMBING TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS III SD YPK ALFA OMEGA WAISAI - Arthur Teny Remiasa; Desti Rahayu; Roni Andri Pramita (CV. ADIBA AISHA AMIRA, 2025)
One of the goals of beginning reading is so that students can read simple words and sentences fluently and precisely. The aim of this research is: to determine the effect of the guided reading method on the beginning reading abilities of third grade students at SD YPK Alfa Omega Waisai. In this research, researchers used quantitative research. The research that will be carried out in this research is experimental research, the type of research is Quasi Experimental type Nonequivalent Control Group Design. The design used in this research is